Studying the Qur’an in the Muslim Academy - Azzuhri, Anggi (Islamic Studies Review, 2023)
Studying the Qur’an in the Muslim Academy | Majid Daneshgar | UK: Oxford University Press, 2020. There is a fundamental problem in studying the Qur’ān in universities and colleges in Muslim-majority countries, which revolves around the significant difficulties in presenting ideas from western intellectuals, or conflicting sects (p. xix). There is a clear trend of negative labelling to describe foreignness, such as orientalism or unreliability of foreign works. This could result in Qur’ānic studies being dragged towards objectivity, orthodoxy, and apologism. This is especially the case if a western contribution to Qur’ānic studies is introduced into the discourse. If the academy is a place where diversity of thought and arguments develops, why does such labelling take place (p. xxii)? This issue serves as a key inspiration for Daneshgar's critical work on the Qur’ān as an academic subject in non-religious institutions.